Post-traumatic growth experience of breast cancer patients: A qualitative systematic review and meta-synthesis - ShiNi Huang; Min Huang; Fang Long; Fang Wang (PLoS ONE, 2025)
Objectives This study aimed to systematically incorporate the post-traumatic growth experience of breast cancer patients and furnish insights for the formulation of targeted psychological care measures. Methods The search period we were ranged from establishing the database to February 2024. We systematically searched four Chinese databases and seven English databases. The focus was on collecting qualitative research literature regarding the post-traumatic growth experience of breast cancer patients. Literature was screened and analyzed using Endnote20 software. Quality evaluation was conducted using the authenticity evaluation criteria (2016 edition) recommended by the JBI. The results were synthesized utilizing the meta-integration methodology established by the Joanna Briggs Institute (JBI) and adhered to the reporting standards delineated in the PRISMA checklist, as well as the ENTREQ reporting guidelines. Results This study encompassed 11 studies, from which 42 themes and 68 sub-themes were extracted. Similar research findings were categorized into 11 new classifications, leading to the formulation of four integrative conclusions: self-reconstruction, enhancement of spirituality and religious beliefs, appreciation of the new philosophy of life, and transformations associated with others. Conclusions Medical professionals should possess a precise comprehension of the concept of post-traumatic growth, and actively encourage patients to engage in deliberate rumination, facilitate emotional release, support effective coping strategies, enhance social support systems, foster post-traumatic growth in patients, and promote their overall well-being. Trial registration Systematic review registration: CRD42024519850.